Trifee objects in e-varieties of locally e-solid semigroups - Hall, T.E.; Yeh, Y.T. (Massey University, 2001)
We construct a modification of Churchill and Trotter’s trifree objects in e-varieties of locally E-solid semigroups, which have the property, for e-varieties of locally inverse semigroups and for e-varieties of Esolid semigroups, of being isomorphic to the bifree objects.